2009
DOI: 10.1093/ndt/gfp487
|View full text |Cite
|
Sign up to set email alerts
|

Guided optimization of fluid status in haemodialysis patients

Abstract: Background. Achieving normohydration remains a non-trivial issue in haemodialysis therapy. Guiding the haemodialysis patient on the path between fluid overload and dehydration should be the clinical target, although it can be difficult to achieve this target in practice. Objective and clinically applicable methods for the determination of the normohydration status on an individual basis are needed to help in the identification of an appropriate target weight.Methods. The aim of this prospective trial was to gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
168
2
8

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(184 citation statements)
references
References 30 publications
6
168
2
8
Order By: Relevance
“…The complementary prognostic information provided by these simple investigations is of major importance for identifying subpopulations that may benefit from a specific intervention and for the design of future randomized trials in patients with chronic kidney disease. Recent studies have demonstrated that brachial pulse pressure, a proxy of arterial stiffness, is an important parameter to take into account when deciding on fluid removal and dry weight (8,9). For the management of hyperphosphatemia, the choice of phosphate binder (calcium-versus noncalcium-containing) may be influenced by the degree of vascular calcification, if the available data on the adverse effect of calcium salts on the progression of vascular calcification and outcome are confirmed (10 -12).…”
Section: Discussionmentioning
confidence: 99%
“…The complementary prognostic information provided by these simple investigations is of major importance for identifying subpopulations that may benefit from a specific intervention and for the design of future randomized trials in patients with chronic kidney disease. Recent studies have demonstrated that brachial pulse pressure, a proxy of arterial stiffness, is an important parameter to take into account when deciding on fluid removal and dry weight (8,9). For the management of hyperphosphatemia, the choice of phosphate binder (calcium-versus noncalcium-containing) may be influenced by the degree of vascular calcification, if the available data on the adverse effect of calcium salts on the progression of vascular calcification and outcome are confirmed (10 -12).…”
Section: Discussionmentioning
confidence: 99%
“…Bioelectrical impedance analysis (BIA) is a method of assessing ECF status by measuring the impedance of the body to applied electric currents of different frequencies 9, 10. Accumulating evidence suggests that strict BIA‐guided fluid management has a beneficial impact on blood pressure, arterial stiffness, left ventricular hypertrophy, and survival in patients undergoing dialysis 11, 12…”
Section: Introductionmentioning
confidence: 99%
“…27,28 Sipahi et al 29 found BIS findings to be related with echocardiographic findings of OH in PD patients.…”
Section: Discussionmentioning
confidence: 98%